Strategi Pemenuhan Kebutuhan Informasi oleh Pemustaka di Perpustakaan Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar - Uswatul Ilmi; Marni Marni (Literatify: Trends in Library Developments, 2021)
Libraries must know and fulfill every information needs of their users. This descriptive study wants to find out strategies for meeting information needs and the obstacles experienced by users in meeting information needs at the Makassar Islamic and Arabic Language College Library (STIBA)? Research data was obtained from informants who are users. The results of the study indicate that the STIBA library has tried to meet the information needs of its users while the constraints experienced by librarians in meeting the needs of users are budget constraints.